Paisagem Litorânea e o Incentivo ao Processo de Verticalização em Guarapari/ES Pelo Turismo de Segunda Residência e Pela Legislação - Fabres, Rafael Pestana (2024)
This dissertation was developed in the Postgraduate Program in Architecture and Urbanism at the Federal University of Espírito Santo, and covers the theoretical field of the verticalization process of the coastal city, with the city of Guarapari, in Espírito Santo, as its object of study. Therefore, the objective of this work was to analyze the formation of the landscape of Guarapari, seeking to understand the process of verticalization that the city went through and still goes through. As a methodological strategy, documentary research was developed, seeking to portray the process of formation of the landscape of Guarapari, highlighting the element of verticalization, relating it to the process of formation of the city and the legislation relating to municipal urban planning. In order to fulfill its objective, the dissertation was structured into six chapters: the first chapter refers to the introduction of the dissertation; the second is intended for conceptual references, presenting a relationship between landscape and coastline, urban policies, tourism and verticalization; the third is dedicated to the presentation of the empirical object, the municipality of Guarapari, bringing the evolution of the formation of the city's landscape, its relationship with second-home tourism and verticalized neighborhoods; the fourth chapter defines a periodization based on the laws relating to urban planning in Guarapari, highlighting those that present content relating to vertical construction potential; the fifth chapter is a synthesis of the periodization of legislation with vertical potential, bringing an evolutionary analysis of the verticalization process of two neighborhoods, Centro and Enseada Azul; and, finally, the sixth chapter focuses on final considerations, in which it was possible to present an understanding of the verticalization process of Guarapari, demonstrating that it was influenced by the proximity to the coast and tourist activity.